Pelatihan Penggunaan Artificial Intelligence (AI) Terhadap Perkembangan Teknologi Pada Pembelajaran Siswa Sma 10 Sukarami Kota Bengkulu - Hanila, Siti; Alghaffaru, Muhammad Afif (Jurnal Dehasen Mengabdi, 2023)
Artificial Intelligence refers to the ability of computer systems to perform tasks that normally require human intelligence, such as natural language processing, decision making, experiential learning, and other cognitive tasks. In many cases, the use of AI technology in learning requires good access to hardware and internet networks. However, not all students have equal access to the necessary devices and connections. This could deepen the educational gap between students who are able to access technology and those who are not. There are also Supervised Machine Learning Research methods, Deep Learning, NLP, and many more. With training in the use of AI for students, it has opened a new leaf for students where the existence of AI has helped students find information quickly and more easily, and with this AI has had a big impact on students and students. Artificial Intelligence (AI) has opened the door to a technological era that is changing the way we interact with the world. The development of AI has affected many aspects of life including industry, education, health, and others. With the ability to process big data, identify complex patterns, and make decisions automatically, AI has helped address challenges and provide new opportunities. However, these developments also present new challenges, such as ethics, data privacy and impact on employment. Seeing the potential for AI to change the job landscape, it is important for individuals to keep their skills up to date. Ongoing training in technology, data analysis, and programming can help prepare people for the more automated jobs of the future.